Initial Public Offering Allocations, Price Support, and Secondary Investors - Fjesme, Sturla Lyngnes (Journal of Financial and Quantitative Analysis, 2016)
Tying initial public offering (IPO) allocations to after-listing purchases of other IPO shares as a form of price support has generated much theoretical interest and media attention. Price support is price manipulation and can reduce secondary investor return. In the past, obtaining data to investigate price support has proven to be difficult. I document that price support is harming secondary investor return using new data from the Oslo Stock Exchange. I also show that investors who engage in price support are allocated more future oversubscribed allocations, whereas harmed secondary investors significantly reduce their future participation in the secondary market.